Prehypertension and Hypertension among Schoolchildren in Brazzaville, Congo - Bertrand Fikahem Ellenga Mbolla; Annie Rachel Okoko; Jean Robert Mabiala Babela; Gaston Ekouya Bowassa; Thierry Raoul Gombet; Suzy-Gisèle Kimbally-Kaky; Benjamin Longo-Mbenza (International Journal of Hypertension)
Background. To determine the prevalence and associated factors of prehypertension (pre-HT) and hypertension (HT) in schoolchildren at Brazzaville (Congo). Methods. This cross-sectional study was conducted from March to May 2011 in five representative urban schools in Brazzaville. American Pediatric Society’s definition of pre-HT and HT was used. The measurement of blood pressure was obtained using auscultator method. Univariable and multivariable analyses were performed to establish associations between blood pressure levels and sociobiographical factors. Results. 603 children were included. The mean age was 11.8±3.6 years (range 5–18 years). The prevalence of pre-HT was 20.7% (n=125). Factors associated with pre-HT were secondary school (P=0.02), private schools (P<0.004), migrants (P=0.03), the obese (P=0.004), high socioeconomic level (P<0.01), and overweight (P=0.02). In logistic regression, the independent determinants of pre-HT were secondary school (P=0.0001), migration (P=0.04), obesity (P=0.004), and overweight (P=0.01). The prevalence of HT was 10.1% (n=61) during the first screening and 3.3% (n=20) in second screening. The independent determinants of HT were obesity (P=0.0001) and overweight (P=0.0001). Conclusion. Pre-HT and HT are emerging as a mass problem in Congolese schoolchildren with urban migration and overweight/obesity to be controlled and prevented.